2019
DOI: 10.4236/ym.2019.32009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gum-Chewing after Cesarean Section on Gastrointestinal Function Recovery: A Systematic Review and Meta-Analysis of Randomized Trials

Abstract: Objective: To evaluate the effect of chewing sugar-free gum on gastrointestinal function recovery after cesarean section. Methods: Randomized controlled trials comparing the use of chewing gum in postoperative recovery with a control group were retrieved from the databases including Pubmed, Cochrane Library, Science Direct, Web of Science, CBM, CNKI, Wanfang and VIP, et al. After screening literatures, evaluating the quality of studies, extracting data, the RevMan5.3 software was used for data analysis. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Zu San Li and Nei Guan were acupunctured to accelerate the gastrointestinal motility in children and adjust the content of hormone and gastric acid [18,19]; meanwhile, Yin Ling Quan and Nei Ting of children were acupunctured to invigorate spleen to eliminate dampness and disperse stagnated hepatoqi. Also, the TCM plasters contained evodia rutaecarpa, dried ginger, and rhizoma corydalis were used, with the functions of promoting qi circulation to relieve pain, warming stomach for dispelling cold, and recuperating depleted yang and invigorating pulse beat, and after herbal combination, they worked on the ganshu, xinshu, and other spots and strengthened the stimulus of acupuncture to children [20][21][22]. TCM emphasizes the dialectical treatment for this category of diseases, so the dialectical treatment of acupuncture is extremely important in treating FD, which can improve the clinical treatment outcome to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Zu San Li and Nei Guan were acupunctured to accelerate the gastrointestinal motility in children and adjust the content of hormone and gastric acid [18,19]; meanwhile, Yin Ling Quan and Nei Ting of children were acupunctured to invigorate spleen to eliminate dampness and disperse stagnated hepatoqi. Also, the TCM plasters contained evodia rutaecarpa, dried ginger, and rhizoma corydalis were used, with the functions of promoting qi circulation to relieve pain, warming stomach for dispelling cold, and recuperating depleted yang and invigorating pulse beat, and after herbal combination, they worked on the ganshu, xinshu, and other spots and strengthened the stimulus of acupuncture to children [20][21][22]. TCM emphasizes the dialectical treatment for this category of diseases, so the dialectical treatment of acupuncture is extremely important in treating FD, which can improve the clinical treatment outcome to some extent.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang, L et al, conducted a meta-analysis on a total of 13 RCTs which included 2233 patients. The results showed that chewing gum after cesarean delivery can effectively shorten the recovery time of bowel sounds, passage of flatus and first defecation [11] . Ajuzieogu, O.V.…”
Section: Discussionmentioning
confidence: 96%
“…The results showed that chewing gum after cesarean delivery can effectively shorten the recovery time of bowel sounds, passage of flatus and first defecation. 6 Ajuzieogu, O.V. et al conducted a study to evaluate the effect of chewing gum on post-operative ileus in 200 women who underwent cesarean sections and found that there was a statistically significant earlier onset of bowel sounds in the chewing group when compared to the control.…”
Section: Discussionmentioning
confidence: 99%